1990
DOI: 10.2134/jpa1990.0415
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and Subsequent Feedlot Performance by Steers That Grazed Different Types of Fescue Pasture

Abstract: Toxicity symptoms manifested by cattle grazing tall fescue (Festuca arundinacea Schreb.) infected with the endophytic fungus Acremonium coenophialum are well documented. However, subsequent feedlot performance by these cattle has been variable. This study was conducted to compared grazing and subsequent feedlot performance of steers that grazed N‐fertilized, A. coenophialum‐infected ‘Kentucky 31’ tall fescue (IF); IF interseeded with ladino clover (Trifolium repens L.; IFL); or endophyte‐free ‘Missouri 96’ tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…Numerous studies have evaluated feedlot performance following a grazing period on E+ fescue. Generally, cattle that previously grazed E+ pastures showed improved gain during a subsequent feedlot period (Coffey et al, 1990;Lusby et al, 1990;Allen et al, 2001;Cole et al, 2001b), but some studies have reported no improvement (Hancock et al, 1987) in feedlot gain or even reduced feedlot gain (Hancock et al, 1988) by calves that grazed E+ pastures previously. However, each of these studies used yearling cattle during post-weaning evaluations on E+ or other non-toxic forages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have evaluated feedlot performance following a grazing period on E+ fescue. Generally, cattle that previously grazed E+ pastures showed improved gain during a subsequent feedlot period (Coffey et al, 1990;Lusby et al, 1990;Allen et al, 2001;Cole et al, 2001b), but some studies have reported no improvement (Hancock et al, 1987) in feedlot gain or even reduced feedlot gain (Hancock et al, 1988) by calves that grazed E+ pastures previously. However, each of these studies used yearling cattle during post-weaning evaluations on E+ or other non-toxic forages.…”
Section: Discussionmentioning
confidence: 99%
“…No advantage in calf weights was detected from a twice weekly compared with a twice monthly rotational grazing system. Body weight gain by calves grazing E+ pastures has been consistently lower compared with calves grazing non-toxic pastures, but the effects of grazing E+ on subsequent animal performance have been variable (Cole et al, 2001b;Hancock et al, 1988;Coffey et al, 1990;Lusby et al, 1990). Furthermore, weaning age and post-weaning management also may impact long-term calf performance (Myers et al, 1999a,b;Thrift and Thrift, 2004;Sexton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…nov. One means for overcoming this problem is to include legumes (Hoveland et al. , 1981; Coffey et al. , 1990; McMurphy et al.…”
Section: Introductionmentioning
confidence: 99%
“…are often deleterious to livestock performance because of toxins produced by association with the endophyte, Neotyphodium coenophialum (Morgan-Jones and Gams) Glenn, Bacon and Hanlin comb. nov. One means for overcoming this problem is to include legumes (Hoveland et al, 1981;Coffey et al, 1990;McMurphy et al, 1990;Chestnut et al, 1991) in the sward. However, introducing legumes into tall fescue swards is difficult, particularly in well-established and endophyte-infected stands (Fribourg et al, 1978;Luu et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Such increases in intake have been associated with a reduced intake of ergovaline (Peters et al 1989). In a complete production system, the depressed performance on endophyte-infected grass may be more than made up by compensatory gain during the subsequent finishing phase on feedlot rations (Coffey et al 1990). …”
Section: Cultivars With or Without Endophytementioning
confidence: 99%